2011
DOI: 10.1371/journal.pone.0022413
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Germ-Cell Marker Genes Are Expressed in All Mouse Pluripotent Cell Types and Emerge Early during Induced Pluripotency

Abstract: Embryonic stem cells (ESCs) generated from the in-vitro culture of blastocyst stage embryos are known as equivalent to blastocyst inner cell mass (ICM) in-vivo. Though several reports have shown the expression of germ cell/pre-meiotic (GC/PrM) markers in ESCs, their functional relevance for the pluripotency and germ line commitment are largely unknown. In the present study, we used mouse as a model system and systematically analyzed the RNA and protein expression of GC/PrM markers in ESCs and found them to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
(56 reference statements)
1
30
0
Order By: Relevance
“…Our data demonstrated that reprogramming of parthenogenetic somatic cells could change the DNA methylation and gene expression status of Snrpn and Ndn. Recent studies have shown that mouse germ cell markers are expressed during induced pluripotency (Xu et al, 2011) and that the Snrpn imprint is erased in fetal germ cells (Smith et al, 2011), which could be an explanation for why erasure or partial erasure of the imprint occurs in mouse miPSCs. Furthermore, alterations in DNA methylation of imprinted genes are maintained when the reprogrammed cells are differentiated into specialized cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that reprogramming of parthenogenetic somatic cells could change the DNA methylation and gene expression status of Snrpn and Ndn. Recent studies have shown that mouse germ cell markers are expressed during induced pluripotency (Xu et al, 2011) and that the Snrpn imprint is erased in fetal germ cells (Smith et al, 2011), which could be an explanation for why erasure or partial erasure of the imprint occurs in mouse miPSCs. Furthermore, alterations in DNA methylation of imprinted genes are maintained when the reprogrammed cells are differentiated into specialized cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Leitch and Smith postulated that germ cells represent a continuous cycle of pluripotency distinguishable just by a naive state in the epiblast and a latent in the germline but not through the expression of pluripotency-regulating genes [25]. Indeed, we could also show that germ cell marker genes are expressed in pluripotent stem cells and arise early in reprogramming [20]. Since Lrrc34 expression arises also very early in the reprogramming time course, it can be a hint for both pluripotency regulator and germ cell gene.…”
Section: Discussionmentioning
confidence: 59%
“…2B). Since all the results till now fit with our hypothesis that Lrrc34 might play a role in establishment and maintenance of pluripotency, we analyzed Lrrc34 expression during the time course of reprogramming by qRT-PCR (samples used for this study are described in [20] Supplementary Fig. S2).…”
Section: Resultsmentioning
confidence: 72%
“…Several lines of evidence provoked the hypothesis that ESCs might derive from PGC-like cells present in the ICM outgrowth. First, explanted cells from the ICM transiently express PGCrelated genes, including Blimp1, Prdm14, Stella, Fragilis, Lin28, c-kit, and Mvh [75,77,78]. Second, specified PGCs are the only cells in the early embryo that maintain (Oct4 and Nanog) or reacquire (Sox2) the expression of pluripotency-associated genes.…”
Section: The Conversion Of Pluripotent Stem Cells Into Pgcs and Gametesmentioning
confidence: 99%
“…With this information in mind, it would be interesting to ask if also the generation of iPSCs from fibroblasts might pass through a germ celllike state. Indeed, it was found that the PGC markers Blimp1, Stella, and Fragilis start to express earlier after viral transduction than pluripotency markers [77]. However, further work is needed to fully understand the significance of this observation.…”
Section: The Conversion Of Pluripotent Stem Cells Into Pgcs and Gametesmentioning
confidence: 99%